2013
DOI: 10.1093/jxb/ert198
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity and population structure of Chinese green foxtail [Setaria viridis (L.) Beauv.] revealed by microsatellite analysis

Abstract: Green foxtail (Setaria viridis) is a new model plant for the genomic investigation of C4 photosynthesis biology. As the ancestor of foxtail millet (Setaria italica), an ancient cereal of great importance in arid regions of the world, green foxtail is crucial for the study of domestication and evolution of this ancient crop. In the present study, 288 green foxtail accessions, which were collected from all geographical regions of China, were analysed using 77 simple sequence repeats (SSRs) that cover the whole g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…This observation is similar to that made in rice [32] and maize [33]. Previous studies of the molecular diversity of Chinese foxtail millet [34] and green foxtail [35] also support this conjecture. A large proportion of the SSRs developed in this study could also be used in S. faberii and S. verticillata , probably because these two species share the AA genome with foxtail millet.…”
Section: Discussionsupporting
confidence: 89%
“…This observation is similar to that made in rice [32] and maize [33]. Previous studies of the molecular diversity of Chinese foxtail millet [34] and green foxtail [35] also support this conjecture. A large proportion of the SSRs developed in this study could also be used in S. faberii and S. verticillata , probably because these two species share the AA genome with foxtail millet.…”
Section: Discussionsupporting
confidence: 89%
“…; Table S1, Supporting information); the general uniformity of this group may help explain an earlier finding that S. viridis in China lacks strong population structure (Jia et al . ) and provides an interesting contrast to the clear population structure of North American S. viridis . This result is also in accordance with many previous studies which pointed out that the domestication centre of S. italica is northern China (Barton et al .…”
Section: Discussionmentioning
confidence: 95%
“…An early population genetic study using 13 isozyme markers and 168 accessions of S. viridis and S. italica from both North America and Eurasia found little differentiation between Eurasia and North America, but did identify distinct northern and southern populations in central North America, on either side of 43.5°N latitude (Wang et al 1995). Jia et al (2013b) used 77 microsatellite markers to survey genetic diversity of 288 S. viridis accessions in China. This study revealed a largely mixed geographic distribution of the genetic diversity of Chinese S. viridis populations and a low level of genomewide linkage disequilibrium (LD).…”
Section: Introductionmentioning
confidence: 99%
“…The wild progenitor of foxtail millet is green foxtail (Setaria viridis), while that of broomcorn millet is uncertain (Zhao 2011). Genetic studies suggest that foxtail millet was first domesticated in the middle reaches of the Yellow River (Wang et al 2012;Jia et al 2013), but archaeological information on this issue is sparse. In the Yellow River region, the earliest evidence for processing wild Paniceae grasses, together with other wild grasses, beans, tubers and bulbs, comes from starch remains found on grinding stones at Shizitan locality 14 (c. 23 000-18 500 cal BP) (Liu et al 2013).…”
Section: Introductionmentioning
confidence: 99%